2022
DOI: 10.1111/1750-3841.16187
|View full text |Cite
|
Sign up to set email alerts
|

Threadfin bream surimi gel containing squid fin protein hydrolysate: Textural properties, acceptability, and volatile profile

Abstract: Gel properties of threadfin bream surimi gels with squid fin protein hydrolysate (SFPH) at various concentrations (0, 1, 2, 3, and 4%; w/w) were determined. The gel without SFPH (CON) had the highest breaking force (BrF) and deformation (DeF) as compared to those with SFPH (p < 0.05). Among the gel with SFPH, gel containing 1 and 2% SFPH (SFPH-1 and SFPH-2, respectively) had the highest BrF, whereas the lowest value was obtained when 4% SFPH was used (SFPH-4) (p < 0.05). The whiteness of all samples was slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In addition, similar values were found between samples containing 0.025 and 0.1% DCE-60 ( p > 0.05). The springiness elucidates the rubberiness of the gel and its capability to spring back after first bite deformation [ 48 ]. A similar trend was noticed for cohesiveness, which measured the force required to overcome the internal bonding of the material [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, similar values were found between samples containing 0.025 and 0.1% DCE-60 ( p > 0.05). The springiness elucidates the rubberiness of the gel and its capability to spring back after first bite deformation [ 48 ]. A similar trend was noticed for cohesiveness, which measured the force required to overcome the internal bonding of the material [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The springiness elucidates the rubberiness of the gel and its capability to spring back after first bite deformation [ 48 ]. A similar trend was noticed for cohesiveness, which measured the force required to overcome the internal bonding of the material [ 48 ]. The gumminess and chewiness almost had a similar trend to the hardness, where the highest values were noticed for the gel with 0.05% DCE-60 added ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a decrease in silver carp surimi gel strength was noticed when 10% soya protein isolate was included as a consequence of the strenuous association of myosin‐to‐myosin interaction (Luo et al, 2008). In a recent study, Singh et al (2022) affirmed that excess small peptides in the protein hydrolysates may have prevented the formation of covalent and non‐covalent bonds during the setting (40°C) of surimi gel by interacting with the unfolded myofibrillar proteins via exposed domains. Given that the S‐CBPE contains a number of short peptides, this may have also been one of the factors contributing to the decrease in breaking force, deformation, and gel strength in T‐5 surimi gels.…”
Section: Resultsmentioning
confidence: 99%
“…The lower thawing loss in the shrimp treated with G15 might be from the hydrophilic peptides' ability to bind with water via hydrogen bonding. Singh et al (2022) reported that adding squid n protein hydrolysate with an amount of 3 and 4% (w/w) in surimi gel from thread n bream could enhance the water-holding capacity of the surimi gel because of the high hydrophilicity of the protein hydrolysate binding with water in the surimi gel. The results might be implied that the mixed phosphates and G15 could protect against water loss after thawing from the shrimp tissue via their water-binding ability.…”
Section: Weigh Gain Of the Shrimp After Treatmentmentioning
confidence: 99%